PTU-021 The use of a novel endoscopically placed radiofrequency probe for the management of malignant bile duct obstruction. (23rd September 2015) - Steel, A; Postgate, A; Vlavianos, P; Khorsandi, S; Habib, N; Westaby, D
Abstract : Introduction: In un-resectable malignant bile duct obstruction the use of self expanding metal stents (SEMS) is the standard technique to ensure continued biliary drainage in patients with life expectancy beyond 3 months. Up to 50% of patients with SEMS will re-present with stent occlusion within the first 6- 8 months, this often leading to significant morbidity and mortality as well as delays in chemotherapy regimes. This study reports the first use in humans of an endoscopically applied radiofrequency treatment prior to insertion of SEMS. The Habib EndoHPB (EMcision UK) catheter is a bipolar radiofrequency ablation (RFA) probe that is 8Fr, 1.8 m long and compatible with standard (3.2 mm working channel) side viewing endoscopes. 2 ring electrodes 8 mm apart at the tip provide local coagulative necrosis over a 2.5-cm length. This study aimed to demonstrate the safety and efficacy of RFA applied within the bile duct by the Habib EndoHPB catheter in patients with malignant biliary obstruction. Methods: Patients with un-resectable pancreatic or bile duct cancer were recruited to this pilot study. At ERCP prior to deployment of SEMS the wire guided Habib EndoHPB catheter was placed under fluoroscopy within the biliary stricture. Based upon prior animal studies ablation was carried out using an RFA generator set at 7–10 W for a time period of 2 min. Depending on the length of the stricture sequential applications were applied to ensure RFA treatment to the entire stricture. After RFA treatment SEMS were deployed as per standard protocols. Immediate and 30-day complications and stent patency were recorded. Results: 15 patients (9 women, mean 70.8 years, 11 pancreatic cancer, 4 cholangiocarcinoma) were recruited between January and October 2009. Deployment of the Habib EndoHPB catheter was successful in all but 1 patient in whom there had been proximal migration of a previously placed plastic stent. Mean procedure time was 44 min, using a median of two RFA applications. SEMS placement was achieved in all cases of successful EndoHPB deployment. Mild pancreatitis developed post-ERCP in one patient. One patient developed a tumour related gallbladder collection, not procedure related, and required cholecystostomy. 30-day patency was maintained in all patients. One patient died with a patent stent within 30 days due to progressive disease. Conclusion: This phase 1 study of endobiliary RFA treatment of malignant biliary obstruction with the Habib EndoHPB catheter demonstrates immediate and 30-day safety and efficacy. Studies to determine the effect of endoscopically applied RFA therapy on long-term biliary stent patency are warranted.